Visceral mast cell tumor in a captive black jaguar (Panthera onca) - De Castro, Márcio Botelho; Werther, Karin [UNESP]; Godoy, Guilherme Sellera [UNESP]; Borges, Vivian Palmeira [UNESP]; Alessi, Antonio Carlos [UNESP] (My University, 2003)
Little is known about neoplasia in the jaguar (Panthera onca), the largest American feline. A captive black jaguar was diagnosed at necropsy with a mastocytic form of visceral mast cell tumor similar to that which occurs in domestic cats. This animal had no previous clinical disease and died during anesthesia for a routine dental treatment.
Keywords: Felidae; Jaguar; Mast cell tumor; Neoplasia; Panthera onca; Pathology; Animalia; Cyamopsis tetragonoloba; Felis catus